Morphological analysis and chlorophyll index of bell pepper cultivars under protected cultivation - Carvalho, Felipe Souza [UNESP]; de Carvalho, Tayna Amaro; dos Santos, Thaís Vitória; Nascimento Casais, Luana Keslley; de Aviz, Rhaiana Oliveira; Maia Nunes, Kelly de Nazaré; Freitas, Luís de Souza; Borges, Luciana da Silva (Lepidus Tecnologia, 2023)
Bell pepper is one of the vegetables that most contributes to the horticultural economy of the state of Para, Brazil, although the state has a low production of this vegetable. The objective of this study was to evaluate the adaptability of bell pepper (Capsicum annuum L.) cultivars grown in protected cultivation under the edaphoclimatic conditions of southeastern state of Para. The experiment was conducted at the Federal Rural University of Amazonia. A randomized block experimental design was used, with four replications. The treatments consisted of 9 bell pepper cultivars: Itapua 501, Yolo Wonder, Chapeu de Bispo Cambuci, Proveito, Amarelo SF 134, Rubi Gigante, Amarelo Alegria, All Big, and Amarelo Satrapo Sais. The parameters analyzed were: plant height (cm); number of fruits per plant; fruit weight (g); transversal (mm) and longitudinal diameters of fruits (mm); leaf area (cm2), width (cm), length (cm), perimeter (cm), and ratio (cm); and chlorophyll a, chlorophyll b, and total chlorophyll. The cultivar Amarelo Satrapo showed greater adaptability to cultivation in the studied region, presenting higher fruit weight, yield, and transversal diameter, leaf area and length, and good morphophysiological development. The cultivars Itapua 501, Amarelo SF 134, and Rubi Gigante showed good performances for morphophysiological parameters. The cultivars that presented the highest chlorophyll indices were Proveito, Itapua 501, All Big, and Amarelo Satrapo. The cultivar Amarelo Satrapo presented the highest adaptation to the climate conditions of southeastern Para.
Keywords: Capsicum annuum L. FCI; Production parameters; Vegetative parameters